Alotamide A, a Novel Neuropharmacological Agent From the Marine Cyanobacterium Lyngbya bouillonii - Soria-Mercado, Irma E. (2009)
[Image: see text] Alotamide A (1), a structurally intriguing cyclic depsipeptide, was isolated from the marine mat-forming cyanobacterium Lyngbya bouillonii collected in Papua New Guinea. It features three contiguous peptidic residues and an unsaturated heptaketide with oxidations and methylations unlike those found in any other marine cyanobacterial metabolite. Pure alotamide A (1) displays an unusual calcium influx activation profile in murine cerebrocortical neurons with an EC(50) of 4.18 μM.